Brilliability and fracture strength of float glass under static and dynamic loads due to radiation heat - Julianto, Eko; Feriansyah, Feriansyah; Wahyu, Wahyu; Gunarto, Gunarto; Sarwono, Eko (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2023)
In this research, steady state and thermal crack analysis was carried out on clear glass exposed to heat radiation with different thicknesses. The analysis process is carried out from the thickness of the glass and testing the temperature variation of the glass testing process to find out the maximum temperature limit of radiation exposure until the glass multiplies thermal crack with steady state analysis of the predetermined ideal heat time. The data collection method used in this study was through testing in an oven where data collection was based on the results of a thermal steady state analysis. The increase in temperature per minute from the first minute was 138.4 ⁰C to the 7th minute or the end was 179.3 °C, from the results research states that in the 7th minute the glass has experienced a crack or crack where the crack starts from the side of the glass which is insulated from radiant heat.